(untitled) (Teacher’s World: Journal of Education and Research, 2024)
Environmental literacy (EL) is considered a key skill for primary students who will be responsible for solving the environmental problems that affect Bangladesh and other countries. This study explored the EL of primary students in urban and rural areas of Bangladesh, using the five EL components: knowledge, skill, awareness, attitude, ability to evaluate, and participation, declared in 1977 Tbilisi conference on environment education. A qualitative approach was used, and data were collected through surveys, focus group discussions, and student interviews. Thematic and descriptive analysis was performed on the findings. The results indicated that urban students had higher EL scores than rural students in all components. The study also suggested the implications of the findings for curriculum developers, policymakers, environmental NGOs, local project planners, and future research. Teacher’s World: Journal of Education and Res arch, 50(1): 21-42